Cosmic Ray Muon Radiography: New Teaching and Educational Media for Geotourism and Museum—A Case Study from Italy - Tommaso Beni; Diletta Borselli; Lorenzo Bonechi; Debora Brocchini; Silvia Guideri; Andrea Dini; Simone Vezzoni; Sandro Gonzi; Giovanni Gigli; Vitaliano Ciulli; Raffaello D’Alessandro; Nicola Casagli (Geoheritage, 2026)
From 2019 to 2023, the MIMA-SITES research project tested the application of muon radiography (muography) at the Temperino mine in the Archaeological and Mining Park of San Silvestro, Italy. Through the collaboration of several partners, i.e., Regione Toscana, National Institute for Nuclear Physics INFN division of Florence, Institute of Geosciences and Earth Resources – CNR, Parchi della Val di Cornia SpA, and the Department of Earth Sciences of the University of Florence, the project has took advantage of the MIMA (Muon Imaging for Mining and Archaeology) muon tracker to test the reliability of muography for archaeological and mining purposes. Focusing on revealing density variations in the mine’s overlying rock mass, this research project identified some unknown cavities and a Cu-Fe-enriched high-density ore shoots. Using the achieved results, multimedia contents were created by employing terrestrial, aerial, and mobile laser scanners (TLS, ALS, and MLS, respectively), unmanned aerial vehicle digital photogrammetry (UAV-DP), and muography data. The results of the muon radiography surveys have been integrated into a new exhibit within the museum pathway of the Temperino mine. This initiative stands as one of the early international examples of utilizing muography to enhance geological heritage within an archaeological and mining park. In addition to emphasizing its geological and archaeological importance, the exhibit sparks interest in local geotourism. This research confirms that incorporating innovative scientific content and multimedia elements can boosts the attractiveness of geological, archaeological, and mining parks, attracting new visitors. Muography can play a key role in cultivating knowledge and curiosity about the distinct geological and archaeological heritage of a site.

Use of muon imaging for enhanced reconstruction of underground cavities and associated stability conditions at a historical mining site - Tommaso Beni; Diletta Borselli; Lorenzo Bonechi; Debora Brocchini; Silvia Guideri; Sandro Gonzi; Tommaso Carlà; Giovanni Gigli; Luca Lombardi; Massimiliano Nocentini; Vitaliano Ciulli; Raffaello D’Alessandro; et al. (Engineering Geology, 2025)

Transmission-Based Muography for Ore Bodies Prospecting: A Case Study from a Skarn Complex in Italy - Tommaso Beni; Diletta Borselli; Lorenzo Bonechi; Massimo Bongi; Debora Brocchini; Roberto Ciaranfi; Luigi Cimmino; Vitaliano Ciulli; Raffaello D’Alessandro; Andrea Dini; Catalin Frosin; Giovanni Gigli; et al. (Natural Resources Research, 2023)
Transmission-based muography (TM) is an innovative imaging technique based on the measurement and analysis of the cosmic ray muons flux attenuation within the target under investigation. This technique allows imaging inner-body density differences and has successfully been applied in a wide range of research fields: geology, archaeology, engineering geology and civil engineering. The aim of this study is to show the reliability of TM as an innovative, noninvasive geophysical method for ore body prospecting and other mining related studies. The measurements were carried out at the Temperino mine in the San Silvestro Archaeological and Mining Park (Campiglia Marittima, Italy), where several magmatic and metasomatic geological units are embodied. Among them, a Cu–Fe–Zn–Pb(–Ag) sulfide skarn complex primarily composed by hedenbergite and ilvaite minerals. Using the acquired muon imaging data obtained with the MIMA (Muon Imaging for Mining and Archaeology) detector prototype (cubic detector of 0.5 × 0.5 × 0.5 m 3 ), the presence of a high-density vein inside the skarn body within the rock volume above the muon detector was identified, localized and interpreted. Applying a back-projection algorithm to the obtained 2D transmission map made it possible to estimate and visualize as point cloud data, in a 2D or 3D environment, the identified high-density body and its relative distance from the detector. The results of this study highlight the potential of muography as a support tool to other geophysical methods in the field of mining exploration.